Antispasmodic effects of Citrus aurantium flowers aqueous extract on uterus of non-pregnant rats - Akram Ahangarpour; Ali Akbar Oroojan; Ashraf Amirzargar; Maryam Ghanavati (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
Background: Citrus aurantium is a small citrus tree, with scented white flowers. The C. aurantium is used in Asian herbal medicine primarily to treat digestive problems.Objective: The goal of this study is to investigate the effect of C. aurantium flower's aqueous extract on uterine contraction in presence of some known uterus stimulants.Materials and Methods: In experimental study 30 virgin Wistar rats 200-300gr were obtained. After laparatomy, a piece of Uterus was dissected out and mounted in an organ bath (10ml) containing De Jalon (29°C) and contracted by KCl (60mM), oxytocin (10mU/ml) and barium chloride (4mM) then the effect of C. aurantium flower's aqueous extract (1-8 mg/ml) on the uterine contractions was investigated. Uterus was separately incubated with propranolol (1M), naloxone (1M) and the role of β-adrenoceptors, opioid receptors were evaluated.Results: Cumulative concentrations of the extract (1-8 mg/ml) decreased KCl, oxytocin and barium chloride induced uterine contractions, dose-dependently (p<0.001). C. aurantium flower's aqueous extract was unaffected on incubation the tissue with propranolol and naloxone.Conclusion: It seems that the extract induced antispasmodic effect mainly via calcium influx blockade. However, neither β-adrenoceptors nor opioid receptors were involved. Since the extract has antispasmodic effect on uterus contraction therefore we can suggest that more study will be necessary to relief dysmenorrheal